Pandemia de COVID-19, as fronteiras pelo mundo e o transporte aéreo na Itália - Thiago Oliveira Neto; Tatiana de Souza Leite Garcia; Eduardo Spinussi (Confins)
COVID-19, classified as an epidemic in December 2019 in China, transcended borders and reached people in other regions of the world, leading the World Health Organization to classify it as a pandemic in March 2020. The spread of this disease in global scale and the negative effects in various dimensions, impacted human, commercial, economic, political relations and flows in geographic spaces. At the moment of this context, this text seeks to describe, through cartographic, photographic and graphic figures, the conditions of the borders around the world and of air transport in Italy.